The psychological underpinnings of finantial risk taking : does consumers' narcissism and entitlement lead to higher financial taking? - Abreu, João Marinho Mendes (2012)
This dissertation was designed to explore if consumers’ narcissism and entitlement lead to higher financial risk taking and if money attitudes explain the link between these two constructs and financial risk. It is hypothesized that the use of money as a source of power and prestige mediates the connection between narcissism and financial risk taking and that the attribution of an intrinsic high value to money mediates the link between entitlement and financial risk taking. To address this questions an online questionnaire was implemented where the studied constructs were measured. The results show that both entitlement and narcissism are predictors of a higher financial risk taking. While entitled people give an intrinsic high value to money narcissists relation to money is mostly explain by their desire to use it to influence other people. Furthermore, the use of money for power and status mediates the relation between narcissism and financial risk taking. On the other hand, an intrinsic value to money has no significant mediation effect on the connection between entitlement and financial risk-taking. These insights can be applied to the field of consumer behavior by clarifying how these two particular personality traits influence the decision making process of taking financial risky products. More specifically banks should take this into consideration when profiling their clients based on risk categorization.